Linguistic study of the text of Uzbek folk epics - Unarova Dilafruz Abdimajit qizi (Global Scientific Publishing, 2025)
This article examines the linguistic study of the text of Uzbek folk oral epics. It also contains information on dialects, lexical-semantic and functional-stylistic features, frequency dictionary, lexicographic research, explanatory dictionary, descriptive-descriptive, artistic-aesthetic function of language units, and authorial lexicography
Keywords: Uzbek folk oral literature; language; dialects